مدى توافر أسس اءدارة الجودة الشاملة في الجامعات الليبية من وجهة نظر الأكاديميين الليبيين الدارسين بماليزيا - Abdalla Abdulkarim Muhammad
This research study aims to study the availability of the basic principles of Total Quality Management (TQM) at the Libyan universities from the perspective of the Libyan academicians in Malaysia, and to seek their suggestions for the enhancement of the management processes at the Libyan universities. In this context, the researcher assumes that there are no substantial differences between the participants’ opinions attributed to the demographic variables of the study such as gender, age, qualification, career, and years of experience. A questionnaire has been adopted as a tool for collecting the data from the study sample which consists of 198 Libyan academicians with a response rate of 90%. Statistical analysis tools, namely, the Mann Whitney and Kruskal test have been used to test the research hypotheses. The research finding show that the availability of TQM basic principles at the Libyan Universities is severely at a very low level although variations in the academicians’ perspectives have been observed and justified as being due to the participants’ ages, qualification, jobs and years of experience. This research study confirms high demands for enhancement and restructuring of the administrative systems at the Libyan universities which allow for the adoption and application of modern management concepts. In light of these findings, this research study recommends that the corresponding authorities should take necessary actions to modify the management regulations and legislation at the Libyan universities. In particular, sufficient flexibility should be granted in order to keep pace with the variations in the surrounding environmental variables. Furthermore, the research study confirms the importance of the provision of financial resources, supplies and facilities to improve the quality of academic services at Libyan universities and to establish measurement principles and benchmarking criteria for the continual quality improvement of the educational process. In a nutshell, this study provides guidelines that can be adopted by the corresponding authorities and future research studies aiming for overcoming the obstacles that hinder the effective application of TQM and for improving the overall quality of educational services in the Libyan universities.